Transformasi Etika Lingkungan Terapan Analisis Manajemen Madrasah Berbasis Nilai-Nilai Al-Qur’an Dan Hadis - Za’far Siddik, Rasyid; Athoillah Yusuf, Ibnu; Yuliany, Yuliany; Haerunisa, Salwa (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Singaperbangsa Karawang, 2025)
The modern ecological crisis demands a transformation in education that is not only theoretical but also applicable and value-based. This study aims to analyze the internalization of Qur'anic and Hadith values in environmental preservation efforts at MA Al-Ikhlas Paninggaran. Using a descriptive qualitative approach, this research explores how sacred texts are transformed into